Development of a method of a variable frequency drive optimal tuning - Romasevych, Y. (Energy and Automation, 2025)
Asynchronous electric drives of a significant number of machines and mechanisms are equipped with frequency inverters (FI). The latter make it possible to significantly increase the control, energy and dynamic properties of the drive. However, at present there is no single approach to solving the problem of optional tunings of the FI, which necessitates the development of such an approach from the standpoint of optimality. This scientific and applied problem has found its solution in this publication. The purpose of the research is to develop a method for optimal tuning of the drive with FI, which would be quite general and would allow to easily find the numerical values of the optional parameters of the FI. Achieving the set purpose involves solving the following tasks: to state the problem of optimal tuning of the FI, to reduce the problem to an unconstrained optimization problem and to provide recommendations on the choice of a method for its solution, to give an example of the application of the developed method for the hoisting mechanism of a bridge crane. To solve the problem, mathematical methods of modeling asynchronous electric machines, optimization and numerical methods were used. To implement optimal tuning of FI, a method of reducing the initial problem to the problem of minimizing a complex nonlinear objective function was developed, which connects the numerical values of the FI options and the selected optimality criterion, as well as constraints on the energy indicators of the variable frequency start of an asynchronous motor. The analysis of the obtained results was carried out according to a complex of dynamic and energy indicators. As a result of the conducted research, it was established that the constraints of the statement part of the problem are met, and the optimization criterion has reached a minimum. The plots of the functions confirmed the acceptability of the results and proved the applicability of the developed method for solving applied problems of FI tuning. Prospects for further research are to expand the class of mechanisms for which optimal tuning of the FI is performed, and to take into account other significant factors in the statement part of such problems.Key words: variable frequency drive, tuning, optimization, hoist mechanism